Ethiopia Urbanization Review : Urban Institutions for a Middle-Income Ethiopia - World Bank Group (World Bank, Washington, DC, 2015)
The urban population in Ethiopia is increasing rapidly. If managed proactively, urban population growth presents a huge opportunity to shift the structure and location of economic activity from rural agriculture to the larger and more diversified urban industrial and service sectors. If not managed proactively, rapid urban population growth may pose a demographic challenge as cities struggle to provide jobs, infrastructure and services, and housing. The central challenge for the Ethiopian Government is to make sure that cities are attractive places in which to work and live, while fostering smart urbanization. Making urbanization a national priority will accelerate Ethiopia’s progress towards reaching middle-income status. The government has already taken steps to make evidence-based, informed decisions for well-managed urban growth, and this report aims to contribute to those efforts.